The Graded Fate of Unattended Stimulus Representations in Visuospatial Working Memory - Sahan, Muhammet I.; Dalmaijer, Edwin S.; Verguts, Tom; Husain, Masud; Fias, Wim (Frontiers in Psychology, 2019)
As in visual perception, information can be selected for prioritised processing at the expense of unattended representations in visual working memory (VWM). However, what is not clear is how this prioritisation degrades the unattended representations. We addressed two hypotheses. First, the representational quality of unattended items could be degraded as a function of the spatial distance to attended information in VWM. Second, the binding strength of an item to its location is degraded as a function of the spatial distance to attended information in VWM. To disentangle these possibilities we designed an experiment in which participants performed a continuous production task in which they memorized a visual array with colored discs, one of which was spatially retro-cued, informing the target location of an impending probe that was to be recalled (Experiment 1). We systematically varied the spatial distance between the cued and probed locations and obtained model-based estimates of the representational quality and binding strengths at varying cue-probe distances. Although the representational quality of the unattended representations remained unaffected by the cue-probe distance, spatially graded binding strengths were observed, as reflected in more spatial confusions at smaller cue-probe distances. These graded binding strengths were further replicated with a model-free approach in a categorical version of the production task in which stimuli and responses consisted of easily discriminable colours (Experiment 2). These results demonstrate that unattended representations are prone to spatial confusions due to spatial degradation of binding strengths in WM, even though they are stored with the same representational quality.